2019
DOI: 10.2147/ott.s212838
|View full text |Cite
|
Sign up to set email alerts
|

<p>A case of primary gastric diffuse large B-cell lymphoma occurring in chronic myeloid leukemia</p>

Abstract: Chronic myeloid leukemia (CML) and Non-Hodgkin Lymphoma (NHL) are two different origins of hematological malignancies, which rarely occur at the same time. Moreover, NHL secondary to CML is common in T cell lymphoma, while NHL of B cell origin is rare. Since 1999, only 22 cases with B cell lymphoma have been reported, of which 4 cases have diffuse large B-cell lymphoma (DLBCL). The lesions of DLBCL were in lymph node, liver, jejunum, and soft palate. To our knowledge, it has no report for the primary gastric D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Sasaki K et al reported 31 (0.2%) CML patients with secondary lymphoma, but their clinical courses are unknown. Table 1 showed the detailed clinical course of lymphomas that developed during TKI treatment in CML patients [10][11][12][13][14][15][16][17] . Among them, imatinib was the most commonly used medication, while there were no reports of patients who were treated with bosutinib.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki K et al reported 31 (0.2%) CML patients with secondary lymphoma, but their clinical courses are unknown. Table 1 showed the detailed clinical course of lymphomas that developed during TKI treatment in CML patients [10][11][12][13][14][15][16][17] . Among them, imatinib was the most commonly used medication, while there were no reports of patients who were treated with bosutinib.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the few reported EBV/HHV8-negative LBCLs arising during imatinib did not resolve with TKI discontinuation, but required active treatment [3,4]. Kaji, D. et al reported the results of a retrospective analysis of a series of HHV8negative primary effusion-based lymphoma, demonstrating a favorable outcome with anthracycline based chemotherapy.…”
mentioning
confidence: 99%
“…Lymphoproliferative disorders (LPDs) are exceptional side effects during CML treatment with TKIs [ 3 , 4 , 5 , 6 , 7 ]. Although clonal expansion of T-large granular lymphocytes (T-LGL) [ 8 ] and reactive follicular hyperplasia [ 9 ] were reported with dasatinib, overt LPDs are extremely rare and have particularly been described in association with first generation TKI imatinib [ 3 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations